2014
DOI: 10.4236/ajps.2014.525385
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Dilutions of <i>Cina</i> for the Control of <i>Meloidogyne incognita</i> in Tomato Plants

Abstract: Considering the importance of the tomato crop and the high costs for controlling Meloidogyne incognita with resistant cultivar or nematicides, it is necessary for the search of new alternatives to manage the root-knot disease. The homeopathy may be an alternative way of control, by inducing plant resistance. This study aimed to evaluate the influence of the homeopathic product Cina at dynamizations 12, 24, 50, 100, 200, and 400 CH (centesimal hahnemanian dilutions) on the number of root galls, eggs and second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Furthermore, when infecting a host plant, the nematode rapidly breaks physiological routes involving most of the major processes, such as respiration, photosynthesis, nutrient translocation, and hormone and water balance (Karssen and Moens, 2006). Some studies have focused on controlling nematode infections in tomato plants (Solanum lycopersicum L.) using highly diluted substances (Sukul et al, 2013;Swarowsky et al, 2014;Mioranza et al, 2017), which may activate plant defense mechanisms and induce resistance. For instance, Mioranza et al (2017) studied the use of Thuya occidentalis in the control of M. incognita in tomato plants, and observed that the dynamization of 100CH can reduce the number of nematodes, while the 24CH and 200CH improved the growth parameters of plants and increased the activity of some plant defense related enzymes, such as peroxidase and phenylalanine ammonia-lyase.. Messchimidt (2013) found that plants infected with M. javanica have increase in photosynthesis until the 60 days after inoculation and after that, there was a reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when infecting a host plant, the nematode rapidly breaks physiological routes involving most of the major processes, such as respiration, photosynthesis, nutrient translocation, and hormone and water balance (Karssen and Moens, 2006). Some studies have focused on controlling nematode infections in tomato plants (Solanum lycopersicum L.) using highly diluted substances (Sukul et al, 2013;Swarowsky et al, 2014;Mioranza et al, 2017), which may activate plant defense mechanisms and induce resistance. For instance, Mioranza et al (2017) studied the use of Thuya occidentalis in the control of M. incognita in tomato plants, and observed that the dynamization of 100CH can reduce the number of nematodes, while the 24CH and 200CH improved the growth parameters of plants and increased the activity of some plant defense related enzymes, such as peroxidase and phenylalanine ammonia-lyase.. Messchimidt (2013) found that plants infected with M. javanica have increase in photosynthesis until the 60 days after inoculation and after that, there was a reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Cina and Thuya (derived from Thuja occidentalis L.), at different Hahnemannian concentrations (c), were assessed in greenhouse conditions against M. incognita parasitizing tomato. [9][10][11] In these studies, homeopathy generally had no or only marginal effect on the nematode. In one instance, nematode reproduction actually increased after treatment with Cina 24, 100, 200 and 400c.…”
Section: Introductionmentioning
confidence: 81%
“…since there are reports of enhanced tolerance, 4,5,11 and reports of no or marginal enhancement. 9,10 Meloidogyne sp. encompasses several species that are highly damaging to plant vascular tissues, hormonal balance, and phenology.…”
Section: Effect Of Cina On Nematode-parasitized Plantsmentioning
confidence: 99%
“…Homeopathic medicines such as Cina (prepared from the flowering meristems of Artemisia nilagirica (Clarke) pamp and Aakashmoni (prepared from the funicles of Acacia auriculiformis A. Cunn) were highly effective in ameliorating mulberry diseases of root-knot (Meloidogyne incognita), leaf spot (Cercospora moricola), powdery mildew (Phyllactinia corylea) and tukra disease (Maconellicoccus hirsutus) as well as improved the plant growth (Datta & Datta, 2011). Swarowsky et al, (2014) and Sukul et al, (2013) reported the effectiveness of potentized Cina reduced the number of root galls, eggs and second-stage juveniles (J2) of Meloidogyne incognita as well as improved the growth of vegetables.…”
Section: Discussionmentioning
confidence: 99%